The effect of quaternary element on the thermodynamic parameters and structure of CuAlMn shape memory alloys - Canbay, C. Aksu; Karagoz, Z. (Springer Heidelberg, 2013)
In this study, the Cu-based shape memory alloys were produced by arc melting. We have investigated the effects of the alloying elements on the characteristic transformation temperatures, enthalpy, entropy values, and the structure of Cu-Al-Mn ternary system. The evolution of the transformation temperatures was studied by the differential scanning calorimetry. The characteristic transformation temperatures can be controlled by the variations in the aluminum and manganese content. Additionally, the effect of magnesium and iron on the transformation temperatures and thermodynamic parameters was investigated in the Cu-Al-Mn ternary system. The addition of the magnesium decreases the characteristic transformation temperatures of the Cu-Al-Mn system, but that of the iron increases. The structural changes of the samples were studied by X-ray diffraction measurements and optical microscope observations. Due to the low solubility of the magnesium, the magnesium addition into the Cu-Al-Mn system forms precipitates in the matrix. It is evaluated that the transformation parameters of the CuAlMn shape memory alloys can be controlled by the change of the alloying elements and the weight percentages of alloying elements.
Keywords: Transformation; Kinetics; Heat